Bacterial Carriage and Antimicrobial Susceptibility Among Intensive Care Unit Nursing Staff at Zliten Teaching Hospital, Libya: A 2013 Cross-Sectional Study - Abdalla Albakosh; Mostafa Mohamed Mohamed Ali; Ibrahim Abdallah Egfier (Tobruk University Journal of Medical Sciences, 2026)
Background: Healthcare-associated infections remain a major concern in intensive care units (ICUs). Nursing staff have frequent direct patient contact, and bacterial carriage in the anterior nares and contamination of the hands may contribute to healthcare-associated transmission. Objective: To describe bacterial carriage in the anterior nares and bacterial recovery from the hands of ICU nursing staff at Zliten Teaching Hospital, Libya, characterise the antimicrobial susceptibility of recovered isolates, and compare paired hand-culture positivity before and after routine handwashing. Methods: A descriptive observational study with paired pre- and post-handwashing hand sampling was conducted during the summer of 2013. Fifty-four specimens were collected from 18 nurses (18 nasal, 18 hand-before-washing, and 18 hand-after-washing). Specimens were cultured aerobically on blood and MacConkey agar. Bacterial identification and antimicrobial susceptibility testing were performed using the BD Phoenix™ 100 Automated Microbiology System. Paired hand-culture positivity was compared using the exact McNemar test. Results: Forty of 54 specimens (74.1%) were culture-positive and yielded 47 isolates because seven specimens were polymicrobial. Coagulase-negative staphylococci (CoNS) accounted for 38/47 isolates (80.9%) and Staphylococcus aureus for 5/47 (10.6%). Hand-culture positivity was 11/18 (61.1%; 95% CI 38.6–79.7%) before washing and 12/18 (66.7%; 95% CI 43.7–83.7%) after washing (exact McNemar test, P = 1.000). Three of five S. aureus isolates were classified as methicillin-resistant S. aureus (MRSA) based on concordant interpretable oxacillin resistance, cefoxitin resistance, and mecA resistance-marker positivity. Four Gram-negative isolates were recovered individually from nasal or post-handwashing specimens. Conclusion: Bacterial recovery was dominated by CoNS, and three of five S. aureus isolates met the available archived laboratory criteria for MRSA. Hand-culture positivity did not differ significantly before and after routine handwashing in this small, paired sample. These findings provide historical, institution-specific cross-sectional data and support the need for contemporary prospective surveillance using standardised sampling, documented hand-hygiene procedures, and current antimicrobial susceptibility standards.